Amine functionalized polyacrylonitrile fibers for the selective preconcentration of trace metals prior to their on-line determination by ICP-MS. Issue 22 (18th May 2021) - Jia, Xiaoyu; Zhao, Junyi; Wang, Jiani; Ren, Hongyun; Hong, Zixiao; Wu, Kun
Abstract : Amine functionalized polyacrylonitrile fibers (PANFs) were designed and utilized as the core adsorbent for solid phase extraction (SPE). The on line SPE-ICP-MS method was established for the separation and determination of V(v ), As(iii ), Sn(iv ), Sb(iii ) and Bi(ii ). Abstract : Amine functionalized polyacrylonitrile fibers (PANFs) were prepared and applied for the simultaneous separation and preconcentration of V(v ), As(iii ), Sn(iv ), Sb(iii ) and Bi(ii ) from environmental water samples in this paper. The functional PANFs were first prepared by nucleophilic substitution reaction between hydroxylamine hydrochloride and polyacrylonitrile fibers, and then the reactant obtained in the first step was subjected to a ring opening reaction with epichlorohydrin, followed by modification with triethylenetetramine (TETA). The structure of the final polymer fibers was analyzed by Fourier transform infrared spectroscopy (FT-IR), and the morphology was characterized by scanning electron microscopy (SEM). A home-made solid phase extraction (SPE) pretreatment column was filled with PANFs, and then online connected with inductively coupled plasma mass spectrometry (ICP-MS) for quantitative determination of metal ions. Under the optimized experimental conditions, the target metal ions were eluted rapidly and quantitatively using 0.3 mol L −1 HNO3 solution. Only with 30 mL sample solution, high enrichment factors of 120 were obtained for V(v ), As(iii ), Sn(iv ) and Sb(iii ), and 115 for Bi(ii ), respectively. The detection limits achieved were low: 1.2, 0.9, 1.7, 1.5 and 2.3 ng L −1 for V(v ), As(iii ), Sn(iv ), Sb(iii ) and Bi(ii ), respectively, and the relative standard deviations (RSDs) were below 3.0%. The advanced fiber materials prepared in this work have the advantages of low cost, environmental friendliness and high adsorption efficiency, and the on-line preconcentration method has greatly improved the analysis efficiency. Finally, the feasibility and accuracy of the method were validated by successfully analyzing Certified Reference Materials (CRMs) as well as lake, river and sea water samples.